2015
DOI: 10.3109/10799893.2015.1075043
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Effect of the co-culture of human bone marrow mesenchymal stromal cells with human umbilical vein endothelial cells in vitro

Abstract: Mesenchymal stem cells (MSCs) give origin to the marrow tromal environment that supports hematopoiesis. These cells present a wide range of differentiation potentials and a complex relationship with hematopoietic stem cells (HSCs) and endothelial cells. In addition to bone marrow (BM), MSCs can be obtained from other sites in the adult or the fetus. Recent studies have shown that cocultured endothelial cells and osteoblasts are mutually promotive in bone tissues repair. In this study, we observed the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…When using stem cells for fabrication of an implant, a central question is how to trigger their differentiation towards a specific cell type. Adding supplements to the culture media (Zuk et al, 2001) or co-culturing with a different cell type (Lin et al, 2016) are well known options to support differentiation towards various cell fates. Establishment of spheroids (Emmert et al, 2013;Kapur et al, 2012) or cell seeding on posts using two-dimensional (2D) micro-engineering (Li and Kilian, 2015) may also act as appropriate strategies.…”
Section: Introductionmentioning
confidence: 99%
“…When using stem cells for fabrication of an implant, a central question is how to trigger their differentiation towards a specific cell type. Adding supplements to the culture media (Zuk et al, 2001) or co-culturing with a different cell type (Lin et al, 2016) are well known options to support differentiation towards various cell fates. Establishment of spheroids (Emmert et al, 2013;Kapur et al, 2012) or cell seeding on posts using two-dimensional (2D) micro-engineering (Li and Kilian, 2015) may also act as appropriate strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio between the co‐cultured cells (1:1 in our study) might also influence angiogenesis or osteogenesis in a significant manner. Lin et al () demonstrated that osteogenic formation is more effective when ECs are co‐cultured with OBs at a ratio of 1:4 and that angiogenesis is more effective at a ratio of 4:1. Another in vitro study demonstrated that a ratio of 5:1 improved vasculogenesis, and a ratio of 1:5 increased mineralization (Shah, Wenke, & Agrawal, ).…”
Section: Discussionmentioning
confidence: 99%
“…Supplements, such as calcium ions [1], bone morphogenetic proteins (BMPs) [2], dexamethasone [3] and bioactive peptides [4,5] in the culture media of stem cells trigger the intended differentiation towards the osteoblast phenotype [6]. Apart from adding supplements, co-cultures [7], microtissues [8] or mechanical stimulation [9][10][11] are promising approaches in this regard. Moreover, the composition of a material acting as a scaffold [12], its surface properties [13], pore size and pore connectivity [14] are essential for the specific commitment of stem cells.…”
Section: Introductionmentioning
confidence: 99%